Faktor-faktor yang berkaitan dengan tingkat perilaku pemeliharaan kebersihan gigi tiruan lepasan akrilik pada lansia di Desa Penatahan Kabupaten Tabanan Bali - Kadek Eka Adhiatmitha; Ni Kd Fiora Rena Pertiwi; Desak Nyoman Ari Susanti (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Loss of teeth when entering the phase of elderly is the impact of the aging process and can be overcome by using denture. Denture users must have attention of hygiene to prevent adverse impacts that might result from the use of the denture that would be affected by health behavior. Health behavior can be measured from the knowledge, attitudes or responses, as well as the actions of a person. Objective: The objective of study is to understand the level of behavior and associated factors towards the level of the acrylic denture hygiene maintenance behavior in elderly in Penatahan Village, Tabanan Regency, Bali. Methods: Descriptive study with cross sectional design was used as the study method. Sampling technique used was total sampling with total 58 samples. Data were obtained using a questionnaire consisting of 15 questions that were read directly to respondents. The level of denture hygiene maintenance behavior of good, less good, and not good were showed by the score of 56-75, 36-55, and <35, respectively. Correlation between sex, age, education level, and the manufacture of the denture towards the level of the denture hygiene maintenance behavior were also be studied. Results: The result of this research exhibited that respondents conducted good behavior were 6 respondents (10.3%), 24 respondents (41.4%) had less good behavior level, and 28 respondents (48.3%) had a level of not good behavior in maintaining the cleanliness of their dentures, and there is correlation between the level of denture hygiene maintenance behavior with sex, education level, and the manufacture of dentures. Conclusion: The level of the acrylic denture hygiene maintenance behavior in elderly in Penatahan Village, Tabanan Regency, Bali, mostly found is very poor, and there was no correlation between level of the acrylic denture hygiene maintenance behavior and age.